Burden of itch in epidermolysis bullosa. (1st July 2014) - Snauwaert, J.J.L.; Yuen, W.Y.; Jonkman, M.F.; Moons, P.; Naulaers, G.; Morren, M.A.
Summary: Background: Itch is an unpleasant feeling that leads to scratching. It is a common, but understudied, problem in patients with epidermolysis bullosa (EB). Objectives: We measured the prevalence and characteristics of itch in the three major forms of EB: generalized EB simplex (EBS), junctional EB (JEB) and dystrophic EB (DEB). Methods: Forty patients with EB were recruited from two tertiary care centres and one patient organization. The sample included 19 patients with EBS, seven with JEB and 14 with DEB. Patients completed the Leuven Itch Scale (LIS), a multidimensional self‐report instrument that quantifies the frequency, duration, severity, distress, consequences and surface area of itch. This instrument has good clinimetric properties. Results: Itch occurred in 85% of the patients, with substantial differences across the subtypes (EBS 74%, JEB 100%, DEB 93%). Itch, in all its dimensions, was most pronounced in patients with JEB and DEB, and less prominent in patients with EBS. The scores were significantly different for itch frequency, severity, distress and surface area, and the overall itch scores were comparable with those of atopic dermatitis. Itch mainly occurred in a hot environment (65%) and when sweating (62%). The most prevalent consequences were difficulty in falling asleep (88%) and lesions from scratching (85%). Differences between the three major subtypes were also observed in terms of circumstances, consequences and sensory characteristics. Conclusions: As expected, itch is common among patients with EB. All aspects of itch measured by the LIS were more severe in JEB and DEB than in EBS.